Increase in antimicrobial resistance and emergence of major international high-risk clonal lineages in dogs and cats with urinary tract infection: 16 year retrospective study. (9th November 2017) - Marques, Cátia; Belas, Adriana; Franco, Andreia; Aboim, Catarina; Gama, Luís Telo; Pomba, Constança
Abstract: Objectives: To evaluate temporal trends in antimicrobial resistance, over 16 years, in bacteria isolated from dogs and cats with urinary tract infection (UTI) and the clonal lineages of bacteria harbouring critical antimicrobial resistance mechanisms. Methods: Antimicrobial susceptibility testing was conducted for 948 bacteria isolated from dogs and cats with UTI (1999–2014). Resistance mechanisms were detected by PCR, namely ESBL/AmpC in third-generation cephalosporin (3GC)-resistant Escherichia coli and Proteus mirabilis, mecA in methicillin-resistant staphylococci, and aac(6′)-Ieaph(2″)-Ia and aph(2″)-1d in high-level gentamicin-resistant (HLGR) enterococci. Resistant bacteria were typed by MLST, and temporal trends in E. coli and Enterobacteriaceae antimicrobial resistance were determined by logistic regression. Results: Enterobacteriaceae had a significant temporal increase in resistance to amoxicillin/clavulanate, 3GCs, trimethoprim/sulfamethoxazole, fluoroquinolones, gentamicin and tetracycline ( P  <   0.001). An increase in MDR was also detected ( P  <   0.0001). 3GC resistance was mainly caused by the presence of bla CTX-M-15 and bla CMY-2 in E. coli and the presence of bla CMY-2 in P. mirabilis . Two major 3GC-resistant E. coli clonal lineages were detected: O25b:H4-B2-ST131 and ST648. The mecA gene was detected in 9.2% ( n  =   11/119) of Staphylococcus spp., including MRSA clonal complex (CC) 5 ( n  =   2) and methicillin-resistant Staphylococcus epidermidis CC5 ( n  =   4). A temporal increase in MDR methicillin-resistant Staphylococcus pseudintermedius was detected ( P  =   0.0069). Some ampicillin-resistant and/or HLGR Enterococcus spp. were found to belong to hospital-adapted CCs, namely Enterococcus faecalis ST6-CC6 ( n  =   1) and Enterococcus faecium CC17 ( n  =   8). Conclusions: The temporal increase in antimicrobial resistance and in MDR bacteria causing UTI in dogs and cats creates important therapeutic limitations in veterinary medicine. Furthermore, the detection of MDR high-risk clonal lineages raises public health concerns since companion animals with UTI may contribute to the spread of such bacteria.